The Impact of Sepaku Semoi Dam Construction on the Reduction of Tengin River Discharge Using the HEC-HMS Model - Bernas Simbolon; Suripin Suripin; Suharyanto Suharyanto (Diponegoro University, 2025)
Floods are one of the most frequent hydrometeorological disasters in Indonesia, particularly in river basin areas. One of the river basins frequently experiencing floods is the Sepaku Watershed (DAS Sepaku). In recent years, the intensity and frequency of flooding in this area have increased. To mitigate future occurrences, flood routing (reservoir routing) calculations are necessary. One of the measures to reduce flooding is the construction of a dam. In response, the Central Government, through the Ministry of Public Works and Housing, has undertaken the development of Sepaku Semoi Dam in Penajam Paser Utara Regency, as part of efforts to optimize water resource potential within the territorial area of the future capital city (IKN). The Sepaku Semoi Dam is projected to supply raw water at a rate of approximately 2,500 liters per second, mitigate flooding, and support tourism. This study aims to analyze flood discharge at the Sepaku Semoi Dam using the HEC-HMS model with the reservoir routing method. The modeling seeks to rapidly estimate flood discharge and assess how changes in storage capacity influence peak discharge conditions, as well as to analyze the impact of dam construction. The flood routing analysis results indicate that the flood reduction for Q1000-year return period is 74.34%, while the outflow discharge for Q50-year return period is 105.7 m³/s, which is lower than the capacity of the Tengin River downstream of the Sepaku Semoi Dam.